Rational Metabolic Engineering Combined with Biosensor-Mediated Adaptive Laboratory Evolution for l-Cysteine Overproduction from Glycerol in Escherichia coli - Xiaomei Zhang; Zhenhang Sun; Jinyu Bian; Yujie Gao; Dong Zhang; Guoqiang Xu; Xiaojuan Zhang; Hui Li; Jinsong Shi; Zhenghong Xu (Fermentation, 2022)
l-Cysteine is an important sulfur-containing amino acid with numerous applications in the pharmaceutical and cosmetic industries. The microbial production of l-cysteine has received substantial attention, and the supply of the precursor l-serine is important in l-cysteine biosynthesis. In this study, to achieve l-cysteine overproduction, we first increased l-serine production by deleting genes involved in the pathway of l-serine degradation to glycine (serine hydroxymethyl transferase, SHMT, encoded by glyA genes) in strain 4W (with l-serine titer of 1.1 g/L), thus resulting in strain 4WG with l-serine titer of 2.01 g/L. Second, the serine-biosensor based on the transcriptional regulator NCgl0581 of C. glutamicum was constructed in E. coli, and the validity and sensitivity of the biosensor were demonstrated in E. coli. Then 4WG was further evolved through adaptive laboratory evolution (ALE) combined with serine-biosensor, thus yielding the strain 4WGX with 4.13 g/L l-serine production. Moreover, the whole genome of the evolved strain 4WGX was sequenced, and ten non-synonymous mutations were found in the genome of strain 4WGX compared with strain 4W. Finally, 4WGX was used as the starting strain, and deletion of the l-cysteine desulfhydrases (encoded by tnaA), overexpression of serine acetyltransferase (encoded by cysE) and the key enzyme of transport pathway (encoded by ydeD) were performed in strain 4WGX. The recombinant strain 4WGX-∆tnaA-cysE-ydeD can produce 313.4 mg/L of l-cysteine using glycerol as the carbon source. This work provides an efficient method for the biosynthesis of value-added commodity products associated with glycerol conversion.